2013
DOI: 10.1093/infdis/jit530
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of Heat Shock Protein 90 Mediated Via a Proximal Promoter Region as Trigger of Caspofungin Resistance in Aspergillus fumigatus

Abstract: Invasive aspergillosis is a deadly infection for which new antifungal therapies are needed. Heat shock protein 90 (Hsp90) is an essential chaperone in Aspergillus fumigatus representing an attractive antifungal target. Using a thiamine-repressible promoter (pthiA), we showed that genetic repression of Hsp90 significantly reduced virulence in a murine model of invasive aspergillosis. Moreover, substituting the A. fumigatus hsp90 promoter with 2 artificial promoters (potef, pthiA) and the Candida albicans hsp90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 38 publications
3
73
0
3
Order By: Relevance
“…Fungal Hsp90 promotes resistance to azole and echinocandin drugs, which has been well demonstrated in the pathogenic yeast Candida albicans (6,10,11). We have previously shown that genetic repression of A. fumigatus Hsp90 abolishes virulence in a murine model of IA (12). Compromising Hsp90-mediated stress responses by genetic modifications of the hsp90 promoter also potentiated the effect of caspofungin and abolished the paradoxical effect of this drug (7,12).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Fungal Hsp90 promotes resistance to azole and echinocandin drugs, which has been well demonstrated in the pathogenic yeast Candida albicans (6,10,11). We have previously shown that genetic repression of A. fumigatus Hsp90 abolishes virulence in a murine model of IA (12). Compromising Hsp90-mediated stress responses by genetic modifications of the hsp90 promoter also potentiated the effect of caspofungin and abolished the paradoxical effect of this drug (7,12).…”
mentioning
confidence: 71%
“…Primers used in this study are listed in Table S1 in the supplemental material. Plasmids pUCGH (27) and pBluescript II SK(Ϫ) containing the hygromycin resistance cassette (12) were used for cloning (see Fig. S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic or pharmacological compromise of Hsp90 function reduces basal echinocandin tolerance and resistance of C. albicans, C. glabrata, and A. fumigatus (Cowen and Lindquist 2005;Cowen 2009;Cowen et al 2009;Singh et al 2009;Singh-Babak et al 2012;Lamoth et al 2014a). Inhibition of Hsp90 reduces echinocandin resistance acquired by mutation in the drug target, and resistance that evolved in the human host Singh-Babak et al 2012).…”
Section: Hsp90mentioning
confidence: 99%
“…112 Recent work in A. fumigatus has shown that Hsp90 is required for the caspofungin mediated paradoxical growth response, and that disrupting Hsp90 circuitry potentiates the antifungal activity of caspofungin. 113 Furthermore, targeting the Hsp90-calcineurin pathway through the combination of respective inhibitors not only resulted in fungicidal activity against azole-resistant A. fumigatus strains but also showed distinct patterns of susceptibility among different fungal species revealing this to be a promising alternative strategy. 17,91 Calcineurin: An attractive antifungal target Due to limited drug efficacy and emerging resistance to drugs, current antifungal classes would benefit from adjunctive agents focused on separate cellular pathways that can be used in combination therapy.…”
Section: Heat Shock Protein 90 and Calcineurin Inhibitors: Another Prmentioning
confidence: 99%